Pengaruh Model Mpscl (Mathematical Problemsolving Cooperative Learning) Terhadap Kemampuan Pemecahan Masalah Geometri Santri - Muhammad Shalihan Warisya Amri (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study examined the effectiveness of Mathematical Problem-Solving Cooperative Learning (MPSCL) in enhancing the geometry problem-solving ability of santri in an Islamic boarding school, particularly on the topics of circle circumference and circle area. A quantitative approach was employed using a onegroup pretest-posttest pre-experimental design. The participants were 15 ninthgrade santri from MTs Darul Hikmah Mumbulsari, an Islamic junior secondary school, selected through purposive sampling. The research instruments consisted of a geometry problem-solving test, a santri response questionnaire, and observation sheets assessing learning implementation and santri activities. Data were analyzed using descriptive and inferential statistics, including the Shapiro– Wilk normality test, paired-samples t-test, N-gain analysis, and effect size analysis (Cohen’s d). The findings revealed a significant improvement in the geometry problem-solving ability of the santri following the implementation of MPSCL. The paired-samples t-test yielded a significance value of 0.000 (p < .05), indicating a statistically significant difference between the pretest and posttest scores. The average N-gain scores were 0.466 for circle circumference and 0.552 for circle area, both categorized as moderate. Furthermore, Cohen’s d values of 2.541 and 4.445 indicated strong practical effects. The santri also demonstrated highly positive responses toward the learning process, while the implementation of learning activities and santri participation were categorized as very good. These findings suggest that MPSCL is an effective instructional approach for enhancing geometry problem-solving ability among santri and supporting meaningful mathematics learning in Islamic boarding school settings.
Keywords: Model MPSCL